A study on the pronunciation errors of some English consonants made by grade 10 students at Giao Thuy High School, Nam Dinh = Nghiên cứu về lỗi phát âm một vài phụ âm tiếng Anh mà học sinh lớp 10 trường THPT Giao Thủy, Nam Định thường mắc. M.A. Thesis Lin - Nguyễn, Văn Hùng (University of Languages and International Studies, 2017)
40 p. + CD-ROM + Tóm tắt